Ekosistem Yang Mempengaruhi Pengembangan Pustakawan - Abdul Rahman Saleh (Jurnal Pustakawan Indonesia, 2020)
The development of a library is strongly influenced by the environment of the users has to be serve. This environment is currently known as the VUCA ecosystem, namely Volatility, Uncertainty, Complexity and Ambiguity. VUCA itself emerged as a result of technological developments which are currently called the industrial revolution 4.0. This paper is a literature review that discusses the influence of the VUCA ecosystem in library development based on the literature and related research reports. Literature is collected both online and printed literature and then discussed. Various papers relevant to the VUCA ecosystem were collected from books, journals, and websites, then analyzed descriptively. Various library developments must consider the VUCA ecosystem so that the services provided by libraries are in accordance with the needs of users in the era of the industrial revolution 4.0. Libraries are entities that are strongly influenced by the VUCA environment or ecosystem. Therefore, in order for libraries to survive in the era of destructive technology that causes VUCA, the librarian as the driving force of the library must have a service breakthrough that can get out of the VUCA trap.